PENGARUH MODEL STAD BERBANTUAN FLIPBOOK TERHADAP HASIL BELAJAR SISWA SMA PADA MATERI KEANEKARAGAMAN HAYATI - Putri, Widya Andari; Ariyati, Eka; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research knew the influence of cooperative learning model type of STAD helped by flipbook on student learning outcomes in material biodiversity at 1st grade SMA Muhammadiyah 1 Ketapang. This research was a quasi experimental with on equivalent control group design. The study sample consisted of two classes namely grade XC as class experiment and grade XB as grade control, the samples took by intact group. The instrument had learned outcome experiment and control class were 15,32 and 13,78. According to t test, tcount> ttable (2,96 > 1,68), it mean there were differences between students taught by cooperative learning model type STAD helped by flipbook with students who taught by conventional model helped by power point. The value of effect size was 0,83 with high category and contribution in 29,67% toward learning outcome in material biodiversity on grade X SMA Muhammadiyah 1 Ketapang. Keywords: Flipbook, Learning Outcome, Material Biodiversity, Cooperatif Learning Model Type by STAD